Barehole Facilities To Support Harmonious Relationship Among Healthy And Prosperous Citizens In Natar Lampung - Bangun Suharti; Ida Nurhida; Ibrahim Besar; Ahmad Riza Faizal (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The impact of the drought has been felt by community members. The long dry season has begun. Residents must immediately mitigate the impact of this long dry season, which usually has a major effect on the supply of clean water in residents' dug wells. The drought has caused residents who do not have boreholes to buy clean water. The problem is that the place where the purchased water is stored is a well that has already dried up. This situation actually absorbs the purchased water, so the water cannot last long in the well. This condition is the basis why this PKM activity must be carried out. This PKM activity was preceded by a pre-survey of the location, followed by discussions with residents and the head of the local RT. Through FGD discussions, the form of activities, location of activities as well as the utilization of the results of this PKM activity were determined. The results of this activity can be utilized by residents as one of the efforts to mitigate drought disasters that occur during the long dry season. Utilization together with residents,will improve harmonious relationships and improve the socio-economy of residents affected by drought in Natar village, South Lampung.